ANALYSIS OF TRAINING NEEDS FOR STUDENTS COLLEGE IN CIREBON CITY - Erawati, Dedet (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Training is needed to create superior human resources. This is, of course, done by analyzing training needs. The urgency of this research is to look at the analysis of training needs for students. Training needs analysis also aims to analyze the gap (differentiation) between expected and actual competencies according to needs and developments. The fundamental difference between this research and previous research is that it focuses on training design and methods, while previous research only focuses on analyzing the training carried out. This research uses a qualitative research method with a phenomenological approach. The results of this research analysis of training needs include preparation, guidelines, references, and objectives of the training program. It is hoped that the things described above will answer the training needs of students in Cirebon. In order to become superior human resources, they can contribute significantly to the development and progress of the city of Cirebon. Of course, the author reminds us that there is a need for synergy between formal education institutions, the government, and institutions with good credibility to collaborate in organizing this training.